Stylistic features and development trends of choreographic stage direction in Kazakhstan - Kussanova, Anipa E.; Kulbekova, Aigul K.; TleubaуevaBalzhan S.; Nikolayeva, Lyudmila A. (Opción, 2020)
The research is devoted to the problem of national art and the formation of the ideological principles of Kazakhstan’s choreographic stage direction. The comparative method and art history analysis were used in order to study the problem. The analysis of the problem of choreography development in Kazakhstan showed that training of stage directors and choreographers is one of the main obstacles to the development of different choreographic directions. Based on the assessment of modern Kazakhstan stage direction and the state of national choreography, it can be concluded that the national heritage is being extensively enriched with new choreographic movements.